Dermoscopic Features of Diaper Dermatoses in Children: A Descriptive Pilot Study - Neha Dhawan; Mohammed Shahana; Mudiam Nagaswetha; Rama M. Cheedirala; Sudharani Chintagunta; G. Narasimha Rao Netha (Indian Dermatology Online Journal)
Background: Diaper dermatoses broadly refer to skin disorders that occur in the diaper area. Dermoscopy is a non-invasive diagnostic tool that magnifies subsurface structures of the skin that are invisible to the unaided eye. Aim: To identify and describe the dermoscopic features of dermatoses in the diaper area. Materials and Methods: A cross-sectional clinical study was conducted, which included 100 children below five years of age with dermatoses in the diaper area. The lesions were initially observed clinically and then under a dermoscope (Dermlite 4, 3GEN Inc., San Juan Capistrano, CA, USA). Findings were recorded and photographed. Results: Of the 100 enrolled children, infectious dermatoses were observed in 46 cases, predominantly comprising scabies and tinea cruris, followed by intertrigo, molluscum contagiosum, and varicella. The most common dermoscopic feature of scabies was a jet wing with a contrail, whereas scaling, red-brown, and grey-brown dots and globules were observed in tinea cruris. Of the non-infectious dermatoses, contact dermatitis and vitiligo were the most common. Dermoscopy revealed irregular-dotted vessels and white structureless areas in cases of contact dermatitis. An absent pigment network and white structureless areas with leukotrichia and white glow were seen in vitiligo, which helped differentiate it from nevus depigmentosus. Limitations: Single-center study with a limited sample size for each condition and histopathological confirmation could not be performed. Conclusion: This study highlights the dermoscopic features of diaper dermatoses and demonstrates the potential of dermoscopy to enhance diagnostic accuracy and optimize patient care without invasive investigations, underscoring its unique role in pediatric dermatology.